THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE ON STUDENTS’ WRITING SKILL - Lastry Forsia (JIPIS, 2018)
AbstractThe aim of this research is to compare the effect of two methods in improving students’ writing skill. Those were between conventional method that was usually used in that school and Cooperative Integrated Reading and Composition (CIRC) technique. This research was conducted at SMAN 15 Tangerang by using experimental research. The population of the research was 321 students and the sample was 76 students from the tenth grade. The data collected by the pre test, treatment and post test. The data was analyzed by using t-test formula. The result of the research showed that t count (2,72) was higher than ttable (2). It could be concluded that there was a significant effect of Cooperative Integrated Reading and Composition (CIRC)Technique in teaching writing recount text on the students’ writing skill. Then, CIRC technique could help students to focus and develop their product writing.Keywords: Cooperative Integrated Reading and Composition, CIRC, experimental research, writing skillAbstrakTujuan penelitian ini adalah untuk membandingkan efektifitas dua metode pembelajaran untuk meningkatkan kemampuan menulis siswa, yaitu antara metode konvensional dan Cooperative Integrated Reading and Composition (CIRC). Penelitian ini dilakukan di SMAN 15 Tangerang dengan metode penelitian eksperimen. Populasi penelitian ini adalah 321 siswa kelas sepuluh dan 76 siswa dipilih sebagai sampel. Data penelitian ini dieoleh dari pre test, perlakuan, dan post-test. Data yang terkumpul dianalisis menggunakan t-test. Hasil penelitian menunjukkan bahwa thitung (2,72) lebih tinggi dari ttabel (2). Dari hasil tersebut, dapat disimpulkan bahwa Cooperative Integrated Reading and Composition (CIRC) memberikan efek signifikan tuntuk meningkatkan kemampuan menulis teks recount pada siswa. Selain itu, teknik CIRC membantu siswa lebih fokus dan dapat meningkatkan kemampuan menulisnya.Kata kunci: Cooperative Integrated Reading and Composition, CIRC, penelitian eksperimen, kemampuan menulis